1968
DOI: 10.1073/pnas.61.2.667
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of rifamycin with bacterial RNA polymerase.

Abstract: The rifamycins specifically inhibit DNA-dependent RNA polymerase (nucleosidetriphosphate: RNA nucleotidyl transferase, DNA-dependent. E.C.2.7.7.6) of bacterial but not of mammalian origin.1' 2 Mizuno et al.3' 4 have shown that streptovaricin, a substance chemically related to the rifamycins, also specifically inhibits DNA-dependent RNA polymerase from E. coli but not from Ehrlich ascites cells. These authors demonstrated that DNA, CTP, Mg++, or Mn++, do not interact with the antibiotic. We have previously repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
125
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(126 citation statements)
references
References 12 publications
1
125
0
Order By: Relevance
“…Wehrli and Staehelin have shown that even in the presence of 0.5 M NH,C1 [6] or 1 M KC1 [2] rifampicin forms a complex with monomeric RNA polymerase which is stable enough to be isolated by gel filtration. and 0.04 mM dithiothreitol for 15 min a t 0 "C (total volume 0.97 ml).…”
Section: Influence Of Freezing and Thawing At High Ionic Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Wehrli and Staehelin have shown that even in the presence of 0.5 M NH,C1 [6] or 1 M KC1 [2] rifampicin forms a complex with monomeric RNA polymerase which is stable enough to be isolated by gel filtration. and 0.04 mM dithiothreitol for 15 min a t 0 "C (total volume 0.97 ml).…”
Section: Influence Of Freezing and Thawing At High Ionic Strengthmentioning
confidence: 99%
“…Several observations point to the binding of the antibiotic to RNA polymerase as the immediate cause of inhibition of RNA synthesis [2,3]. Previous studies have made it unlikely that rifamycins are bound to the enzyme by a covalent bond [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2) produced by an actinobacterium Amycolatopsis mediterranei [4]. In general, rifamycins bind to the b-subunit of the RNA polymerase, and inhibits mRNA transcription [5,6]. Introduction of rifampicin in late 1960s led to considerable fall in the mortality rate due to TB and since then it has been used as the first line of drug.…”
Section: Introductionmentioning
confidence: 99%
“…Together with biochemical evidence (5,34) this indicates that streptolydigin inhibits RNA synthesis by interaction with the RNA polymerase rather than by binding to the template as does actinomycin D (27). In contrast to rifampin, which acts on initiation of transcription (36,41), streptolydigin has been shown to interfere with RNA chain elongation (5). Cassani et al (5) also showed stabilization of the RNA-enzyme-deoxyribonucleic acid (DNA) complex in vitro when using purified RNA polymerase and T4 DNA; the inhibition of RNA chain elongation is reversible in vitro (34).…”
mentioning
confidence: 99%